2020
DOI: 10.1029/2019wr026449
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Modeling of River‐Floodplain‐Reservoir Inundation Dynamics in the Mekong River Basin

Abstract: Numerous studies have examined the changes in streamflow in the Mekong River Basin (MRB) using observations and hydrological modeling; however, there is a lack of integrated modeling studies that explicitly simulate the natural and human-induced changes in flood dynamics over the entire basin.Here we simulate the river-floodplain-reservoir inundation dynamics over the MRB for 1979-2016 period using a newly integrated, high-resolution (~5 km) river hydrodynamics-reservoir operation model. The framework is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 98 publications
(168 reference statements)
2
57
0
Order By: Relevance
“…Analysis of the hydrological alterations parameters shows that flow regime alteration is likely due to the operation of reservoirs. However, the magnitude and intensity of the alterations vary widely based on reservoir characteristics, location and operation policies, which has also been pointed out in other studies [58][59][60][64][65][66]. Our results indicated that, in addition to reservoir features, the location of the reservoir is also a significant factor for variations of the rate of hydrologic alterations, as the basin is characterized by wide variation in topography and physiography with complex climatic conditions.…”
Section: Ha Due To Reservoir Operations and Climate Changesupporting
confidence: 83%
“…Analysis of the hydrological alterations parameters shows that flow regime alteration is likely due to the operation of reservoirs. However, the magnitude and intensity of the alterations vary widely based on reservoir characteristics, location and operation policies, which has also been pointed out in other studies [58][59][60][64][65][66]. Our results indicated that, in addition to reservoir features, the location of the reservoir is also a significant factor for variations of the rate of hydrologic alterations, as the basin is characterized by wide variation in topography and physiography with complex climatic conditions.…”
Section: Ha Due To Reservoir Operations and Climate Changesupporting
confidence: 83%
“…These products are generated with different source data, methods, spatial resolution and time slots (Leyk et al, 2019). Smith et al (2019) evaluated the population exposure to a 1-in-100 year flood in 18 developing countries. The total exposed population ranges from 101 to 134 million when using three different products, but with an up to 60 % difference in population in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, representing the flood defenses remains a big challenge because the global data for flood defenses are strongly limited (Sampson et al, 2015). Attempts to improve CaMa-Flood by integrating the dam regulation (Shin et al, 2020) and levees (Tanaka and Yamazaki, 2019) have been tested at a regional scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Res, we acquired data on storage-depth relationship, maximum surface extent, dam design specifications, and rule curves. The storage-depth relationship is modeled with Liebe's method 51 , the most common approach in large-scale studies [52][53][54] . The maximum surface extent of each reservoir is estimated by extracting surface water profiles from Landsat TM and ETM+ imagery, while the dam design specifications are obtained from the Mekong River Commission and the Electricity Generating Authority of Thailand-and complemented, where necessary, with information retrieved from other databases.…”
Section: Discussionmentioning
confidence: 99%